Barrett's Esophagus and Cardiac Intestinal Metaplasia: Two Conditions within the Same Spectrum. (2008) - White, Nicole; Gabril, Manal; Ejeckam, Gershon; Mathews, Maria; Fardy, John; Kamel, Fady; Doré, Jules; Yousef, George M
Abstract : BACKGROUND: Immunostaining for cytokeratin 7 (CK7) and cytokeratin 20 (CK20) has a characteristic pattern in Barrett's esophagus (BE), but reports regarding its sensitivity and specificity are inconsistent. Intestinal metaplasia of the gastric cardia (CIM) is histologically similar to BE, but with no abnormal endoscopic findings. OBJECTIVES: To evaluate the sensitivity and specificity of a semi-quantitative CK7/CK20 immunostaining pattern for the diagnosis of BE, and to further elucidate the pathogenesis of CIM. METHODS: Tissues were examined by hematoxylin and eosin and periodic acid schiff/alcian blue stains, and then were immunostained with CK7 and CK20 antibodies. Correlations with other clinical parameters were statistically analyzed. RESULTS: When values were revised based on follow-up data and auxiliary testing, all BE cases (100%) displayed the characteristic BE CK7/CK20 immunostaining pattern, compared with 66% of CIM cases. In the subgroup of patients who were endoscopically and immunohistochemistry-positive but histologically negative, all patients except for one had documented BE when clinical history, auxiliary testing and follow-up were evaluated. There were no statistically significant differences between BE and CIM regarding Helicobacter pylori infection or the type of metaplasia (complete versus incomplete). The sensitivity of the CK7/CK20 pattern reached 100% in the subgroup of CIM patients with a history of acid reflux. Of 26 cases of CIM where follow-up was available, four cases (15%) progressed to BE, and one developed dysplasia. All four cases showed the BE pattern of CK7/CK20 staining and were negative for H pylori infection. CONCLUSIONS: A semiquantitative CK7/CK20 pattern can be used to confirm BE even in the absence of histological evidence. The subgroup of CIM with acid reflux may develop into BE and may need closer follow-up.